Socioeconomic Influences to the School Performance: Case Study of O-NET Test Result in the Provincial Level - Tonboot, Sila (Journal of Community Development Research (Humanities and Social Sciences), 2017)
The article was aimed to estimate the influences of socioeconomic factors towards the O-NET test results in Thailand. The purpose of this research was to study the effect of socioeconomic status toward the O-NET test results of the 6 th grade, 9 th grade, and 12 th grade in Thailand. A simple linear regression was adopted to analyze the cross sectional data at the provincial level. The data was retrieved from various surveys by the National Statistical Organization during 2010 such as the Household Expenditure survey, Labor Force survey and Employment survey. The results found that the household income and household expenditures were unable to describe the test score. The internet accessibility and unemployment provided significantly effects to the test results. Nevertheless, the absence of the relationship between the income and the school performance may be diluted by the application of average score as a provincial proxy. In this study, the household income and expenditure took no part in the education performance in the provincial level. To overcome the diluted scores, using of the small area estimation may point out the effect of the socioeconomic status toward the O-NET test scores explicitly.
Keywords: School Performance, Socioeconomic Factors, O-NET Test